Breast cancer screening programs: Review of merits, demerits, and recent recommendations practiced across the world. Issue 2 (June 2017) - Shah, Tajammal Abbas; Guraya, Shaista Salman
Abstract: Breast cancer screening is defined as the evaluation of symptom free, otherwise healthy looking females of child bearing age or postmenopausal women for early detection of breast cancer. Screening mammography is the most common and widely practiced breast cancer screening modality across the world. The other modes of breast cancer screening being practiced across the world are: breast self-examination (BSE), clinical breast examination (CBE), digital breast tomosynthesis (DBT), ultrasonography (USG), magnetic resonance imaging (MRI), and identification of certain genetic oncogenes. The major merits of breast cancer screening programs are: early diagnosis, sorting out and prevention of risk factors, and timely treatment to lessen the morbidity (5 years localized stage survival rate is 99%, regional disease 84% while metastatic breast cancer 5 year survival rate is 23%); it also reduces overall 20% mortality rate. The major demerits of breast cancer screening are: overdiagnosis (19% from the perspective of a woman invited to screening), high cost, ionizing radiation (lifetime attributable risk to develop breast cancer is 3/10, 000), false positive biopsy recommendation (about 8/1000), false negative results 11/10, 000), and their consequences. Worldwide, most of the countries recommend biennial screening for breast cancer at 50–74 years of age. However, some countries recommend screening mammography earlier, starting at the age of 40 years until 70–74 years based on higher breast cancer incidence rate in those countries. This article provides a detailed review of merits, demerits, and recent recommendations for screening programs being practiced across the world.